Prevalence and Predictors of COVID-19 Vaccine Hesitancy among Health Care Workers in Tertiary Health Care Institutions in a Developing Country: A Cross-Sectional Analytical Study - Chinedu Anthony Iwu; Pius Ositadinma; Victor Chibiko; Ugochukwu Madubueze; Kenechi Uwakwe; Uche Oluoha (Advances in Public Health)
Background. The coronavirus disease 2019 (COVID-19) pandemic highlighted the challenges and impact of vaccine hesitancy and the role of health care institutions in mounting an effective pandemic response. The study objective was to determine the prevalence and predictors of COVID-19 vaccine hesitancy among health care workers in tertiary health care institutions in Nigeria. Methods. A cross-sectional analytical design that used convenience and snowballing techniques to enroll 347 health care workers from tertiary health care institutions in Imo State, Nigeria, from September 28 to October 14, 2021. Data was collected using a structured online questionnaire and bivariate and multivariate analyses were done using SPSS at a level of significance set at p≤0.05. Result. The prevalence of vaccine hesitancy was 35.4%. HCWs of the Pentecostal faith (aOR: 2.52) and males (aOR: 2.72) were significantly more likely to be COVID-19 vaccine hesitant. About 30% of the respondents reported that they trusted information from the Internet and social media relating to COVID-19 and its vaccine. However, respondents who felt there was enough information about the vaccine and its safety were more than two and a half times more likely to be vaccine-hesitant (aOR: 2.77). About 20% and 31% of the respondents, respectively, stated that the government has an ulterior motive and that they did not trust the vaccine manufacturers. However, respondents who do not trust the government were more than two and a half times more likely to be COVID-19 vaccine hesitant (aOR: 2.69). Conclusion. The issues of vaccine hesitancy among health care workers in a developing country appear to be fundamental and very challenging to resolve. Therefore, the approach of instituting government vaccine uptake mandates for health care workers may be the solution for tackling vaccine hesitancy in health care institutions.